Penerapan Media Sosial Sebagai Strategi Pemasaran UMKM Telur Asin Pak Dapin di Kabupaten Karawang - Febrianti, Mutiara; Savitri, Citra; Faddila, Syifa Pramudita (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The expansion of IT has altered the marketing landscape in recent years. In today's era of cutthroat corporate rivalry, a company's marketing plan is a potent tool. Businesses might collapse if they don't have a solid plan in place. The purpose of this study is to examine how UMKMPak Dapin's salted eggs have been marketed on social media in an effort to boost sales. Interviews with company leaders and analyses of relevant documents are the backbone of qualitative research methods. According to the findings, Pak Dapin's salted egg UMKM has effectively implemented a number of marketing strategies, such as developing salted egg products with the advantage of salted eggs into two flavor variants (original salted eggs and grilled salted eggs), setting prices based on market segments, using social media as promotion, and establishing cooperation with local and out-of-town partners for distribution. Products may keep their quality via structured manufacturing methods. By developing and implementing plans for each component of the UMKM marketing mix, the salted egg company Pak Dapin used social media to boost sales. This study has important repercussions for other UMKM looking to get a competitive edge and maintain development in their businesses by using social media marketing.